Middle class values in India and Western Europe - Ahmad, Imtiaz; Ahmad, Imtiaz, 1940-; Reifeld, Helmut; Konrad-Adenauer-Stiftung. (New Delhi : Social Science Press : Distributed by D.K. Publishers and Distributors, 2001)
Contributed papers presented at a workshop held on March 7-10, 2001.
"Konrad Adenauer Foundation."
Includes bibliographical references.
Keywords: Middle class -- Europe, Western -- Congresses; Social values -- India -- Congresses; Social values -- Europe, Western -- Congresses